2021
DOI: 10.5109/4372255
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Collective Action, and the Development of Agritourism for Sustainable Agriculture in Rural Indonesia

Abstract: This study investigates social capital, collective action, agritourism, and sustainable agriculture in rural areas of Indonesia. Social capital, consisting of trust, networks, and norms, would encourage collective action to increase the development of village tourism/agritourism. Therefore, this study proposed more than one latent variable to define this social phenomenon and used a structural equation model (SEM) to predict those variables from the observed variables. The observed variables were two demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…Several studies (e.g., Nyaupane and Thapa, 2010;Myeza et al, 2010;Nepal, 2003, Gumede andNzama, 2019a) have argued that this exclusion is a threat to comprehensive sustainable ecotourism development as the results are often issues such as environmental degradation, marauding, and criminal offenses against tourists. Local community participation therefore remains a basic necessity for the operationalisation, management, and sustainability of ecotourism projects (Prameka et al, 2021;Nugraha et al, 2021;Xiong et al, 2021).…”
Section: Literature Review Comprehensive Participatory Approach and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (e.g., Nyaupane and Thapa, 2010;Myeza et al, 2010;Nepal, 2003, Gumede andNzama, 2019a) have argued that this exclusion is a threat to comprehensive sustainable ecotourism development as the results are often issues such as environmental degradation, marauding, and criminal offenses against tourists. Local community participation therefore remains a basic necessity for the operationalisation, management, and sustainability of ecotourism projects (Prameka et al, 2021;Nugraha et al, 2021;Xiong et al, 2021).…”
Section: Literature Review Comprehensive Participatory Approach and S...mentioning
confidence: 99%
“…They attribute this to a top-down planning and management approach, arguing that this model poses a main barrier to sustainable relationships among ecotourism stakeholder groups (Murphy, 1985). While an extensive body of academic literature (Gumede and Nzama, 2020;Ying and Zhou, 2007;Chili and Ngxongo, 2017;Prameka et al, 2021;Xiong et al, 2021;Nugraha, 2021) highlights the significance of local community participation in ecotourism development, numerous studies (e.g., Mustapha et al, 2013;Marzuki et al, 2012;Dogra and Gupta, 2012;Snyman, 2016;Wang et al, 2015;Wen and Ximing, 2008) found manipulative participation to be dominant in most tourist destinations, including some in South Africa. Moreover, there is a paucity of academic research in the field of sustainable ecotourism development in KwaZulu-Natal.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, precision farming is a management strategy that uses information technology to improve agricultural quality and production 22) . Those may develop either sustainable agriculture or income for communities 23) .…”
Section: Smart Farming Conceptmentioning
confidence: 99%
“…Fires occurred in several regions in Indonesia, such as Sumatra and Kalimantan, which attracted worldwide attention because the smoke haze pollution reached neighboring countries. Forest fires are not new to Indonesia's forests and are an essential environmental problem 8), 9) . Forest and land fires occur due to 2 (two) main factors, namely natural factors and uncontrolled human activity factors 3) .…”
Section: Introductionmentioning
confidence: 99%